Anaesthetic management of a Baringo giraffe (Giraffa camelopardalis rotschildi) undergoing mandibular fracture repair on two occasions. Issue 1 (4th March 2017) - Cruz Benedetti, Inga‐Catalina; Chenet, Baptiste; Douay, Guillaume; Portier, Karine
Abstract : A four‐year‐old zoo Baringo giraffe ( Giraffa camelopardalis rothschildi ) was anaesthetised twice for surgical repair of an open fracture of the right mandible. On both occasions, xylazine was administered intramuscularly via a compressed CO2 ‐powered blowpipe‐pistol followed by etorphine and acepromazine. General anaesthesia was induced with ketamine intravenously and the giraffe's trachea was intubated. A surgical plane of anaesthesia was maintained with additional ketamine, xylazine, etorphine and acepromazine. During the second anaesthetic episode, a right inferior alveolar nerve block was performed and a constant rate infusion of lidocaine administered to enhance perioperative analgesia. Vital parameters remained within normal ranges for anaesthetised giraffes. At the end of the procedures, the animal received naltrexone, atipamezole and diprenorphine. The giraffe stood up smoothly in one single attempt the first time but showed mild muscle weakness and required two attempts to stand the second time. Flunixine meglumine was administered for postoperative analgesia after both procedures.